HUBUNGAN PENGETAHUAN TENTANG OBAT TANPA IZIN EDAR DENGAN SIKAP PEMBELIAN OBAT SECARA ONLINE PADA SISWA SMA MUHAMMADIYAH KUDUS - Fitria Maulina; Zaenal Fanani; Bintari Tri Sukoharjanti (JOURNAL OF BAJA HEALTH SCIENCE, 2026)
The development of digital technology has increased online drug purchasing behavior among adolescents, including the risk of purchasing drugs without distribution permits. Knowledge is considered an important factor influencing attitudes toward online drug purchasing. This study aimed to determine the relationship between knowledge about drugs without distribution permits and attitudes toward online drug purchasing among students of SMA Muhammadiyah Kudus. This research used an analytic observational method with a cross-sectional approach. The sample consisted of 65 students selected using purposive sampling technique. Data were collected using questionnaires measuring knowledge and attitudes. Data analysis was performed using the Spearman Rank test. The results showed that most respondents had high knowledge and positive attitudes toward online drug purchasing. Statistical analysis showed a significance value of 0.138 (p>0.05) with a correlation coefficient of 0.186. These results indicate that there was no significant relationship between knowledge about drugs without distribution permits and attitudes toward online drug purchasing among students of SMA Muhammadiyah Kudus, although the relationship direction was positive and very weak.